Disability, Citizenship and Uncivilized Society: The smooth and nomadic qualities of self-advocacy - Roets, Griet; Goodley, Dan (Disability Studies Quarterly, 2008)
People with the label of "intellectual disabilities"1 are often objectified and devalued by master narratives of deviance, tragedy and lack. In this paper, we draw on poststructuralist and feminist resources (e.g. Deleuze & Guattari 1987 and Braidotti 1994, 2002, 2006a) to argue that a disabling society is uncivilized in ways that block the becomings of citizenship. We draw upon our work with self-advocacy groups in England and Belgium where self-advocates open up different life worlds. We shed light on their politics of resistance and resilience, and map how they, as politicized citizen subjects, move in a web of oppressive disability discourses. However, we suggest, as nomads, they set foot on the landmarks of their lives in a never-ending search for smooth spaces in which something different might happen.